2002
DOI: 10.1002/1521-3773(20020802)41:15<2808::aid-anie2808>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

MoV/Pyrophosphate Polyoxometalate: An Inorganic Cryptate

Abstract: Polyoxometalate chemistry continues to be a subject of great interest, since the wide and fascinating variety of structures and properties of these objects gives rise to numerous applications. [1] Polyoxoanions containing phosphato groups constitute the largest class of heteropolyanions, with structures ranging from molecular complexes to extended frameworks. [2] In contrast, very few polyoxometalate-containing polyphosphato groups have been structurally characterized. In 1994, Kortz and Pope reported the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…[31][32][33] This synthetic strategy has, however, only been exploited for purely inorganic reduced POMs, while the use of reduced hybrid organic-inorganic polyoxometalates could lead to antibacterial materials combining the properties of AuNPs, POMs and biologically active organic substrates. The chemistry of POMs structured by bisphosphonate ligands (BPs) has been widely studied, [34][35][36][37][38][39][40] and in particular several molybdenum, tungsten and vanadium complexes incorporating the alendronate (Ale) ligand [O 3 PC(C 3 H 6 NH 3 )OPO 3 ] 4À have been obtained. 20,41 Interestingly, it has also been shown that alendronate itself increases antibiolm effects when combined with bioactive glass.…”
mentioning
confidence: 99%
“…[31][32][33] This synthetic strategy has, however, only been exploited for purely inorganic reduced POMs, while the use of reduced hybrid organic-inorganic polyoxometalates could lead to antibacterial materials combining the properties of AuNPs, POMs and biologically active organic substrates. The chemistry of POMs structured by bisphosphonate ligands (BPs) has been widely studied, [34][35][36][37][38][39][40] and in particular several molybdenum, tungsten and vanadium complexes incorporating the alendronate (Ale) ligand [O 3 PC(C 3 H 6 NH 3 )OPO 3 ] 4À have been obtained. 20,41 Interestingly, it has also been shown that alendronate itself increases antibiolm effects when combined with bioactive glass.…”
mentioning
confidence: 99%
“…The successful isolation of compound 1 relies on the employment of a hydrothermal technique. Hydrothermal synthesis has recently been proved to be a particularly effective method for the preparation of new organic–inorganic hybrid materials 2,6–15. Exploitation of hydrothermal conditions provides a paradigm shifting from the thermodynamics to the kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…{Mo 2 O 4 } 2+ clusters with metal d electrons localised in single metal–metal bonds occupy a prominent position among the polyoxometallates, which continue to be a subject of great interest because of their potential applications ranging from catalysis to medicine 1. Their basic building blocks, dinuclear {Mo 2 O 4 } 2+ moieties (Scheme ) with a well‐defined geometry,2,3 can assemble in many different ways and lead to a variety of metal oxide cores, as illustrated by some recently prepared clusters, i.e., [(Mo 2 O 4 ) 4 (OMe) 6 (MeOH) 4 Cl 2 ],4 bimetallic alkoxides [M 2 (Mo 2 O 4 ) 2 (O i Pr) 14 ] (M = Ta, Nb),5 [(Mo 2 O 4 ) 6 (μ 2 ‐SO 3 ) 12 (μ 3 ‐SO 3 ) 4 ] 20– ,6 [Na 4 (H 2 O) 6 {(Mo 2 O 4 ) 10 (P 2 O 7 ) 10 (CH 3 COO) 8 (H 2 O) 4 }] 24– ,7 [(Mo 2 O 4 ) 3 (O 3 PCH 2 PO 3 ) 3 (MoO 4 )] 8– ,8 [Na(H 2 O) 2 {(Mo 2 O 4 ) 4 (O 3 PCH 2 PO 3 ) 4 (CO 3 ) 2 }] 11– ,9 and a series of nano‐sized, mixed‐valence Mo V /Mo VI acetate complexes 10. Theoretical calculations have been performed on some of these species in order to understand the bonding of such complex architectures 11.…”
Section: Introductionmentioning
confidence: 99%